The relationship between the plasma concentration of blonanserin, and its plasma anti-serotonin 5-HT2A activity/anti-dopamine D2 activity ratio and drug-induced extrapyramidal symptoms - Suzuki, Hidenobu; Gen, Keishi (Psychiatry and clinical neurosciences, 2012)
Aims:  Blonanserin is a second‐generation antipsychotic that was developed in Japan. We investigated the relationships between plasma concentration, the plasma anti‐5‐HT2A activity/anti‐D2 activity (S/D) ratio and extrapyramidal symptoms (EPS) in blonanserin dosing. Methods:  The subjects were 29 outpatients with schizophrenia. We assessed EPS using the Drug‐Induced Extrapyramidal Symptoms Scale (DIEPSS). The plasma concentrations were measured by high performance liquid chromatography, and the plasma anti‐D2 and anti‐5‐HT2A activities were measured by [3H]‐spiperone and [3H]‐ketanserin radioreceptor assays. Results:  The results revealed that there were significant correlations between both the plasma concentration and the DIEPSS total score (P < 0.05). A negative correlative tendency was found between the S/D ratio and the DIEPSS total score. Furthermore, the plasma concentrations were divided into a low plasma concentration group and a high plasma concentration group, and the S/D ratios were divided into a low S/D ratio group and a high S/D ratio group. We then compared each group based on the DIEPSS total scores. The score in the high plasma concentration‐low S/D ratio group was significantly higher than in the high plasma concentration‐high S/D ratio, low plasma concentration‐high S/D ratio and low plasma concentration‐low S/D ratio groups (P < 0.05 for all). Conclusions:  These findings indicate that the incidence of EPS during treatment with blonanserin is mainly determined by plasma concentration, but the incidence of EPS may be inhibited when anti‐5HT2A activity is predominant over anti‐D2 activity.